2014
DOI: 10.1093/ajh/hpu003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypertension, Awareness, Treatment, and Control in the Hispanic Community Health Study/Study of Latinos

Abstract: These findings indicate a significant deficit in treatment and control of hypertension among Hispanics/Latinos residing in the United States, particularly those without health insurance. Given the relative ease of identification of hypertension and the availability of low-cost medications, enabling better access to diagnostic and treatment services should reduce the burden of hypertension in Hispanic populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
130
4
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(147 citation statements)
references
References 9 publications
7
130
4
2
Order By: Relevance
“…More than half (60%) of the studied hypertensive patients had controlled blood pressure, slightly higher rates when compared to other national studies (4,(17)(18)(19) . Among the bio-social characteristics of hypertensive patients that were associated with the control, the fact that women are more controlled also coincides with the results of other studies (20)(21)(22) .…”
Section: Discussioncontrasting
confidence: 49%
“…More than half (60%) of the studied hypertensive patients had controlled blood pressure, slightly higher rates when compared to other national studies (4,(17)(18)(19) . Among the bio-social characteristics of hypertensive patients that were associated with the control, the fact that women are more controlled also coincides with the results of other studies (20)(21)(22) .…”
Section: Discussioncontrasting
confidence: 49%
“…3 Healthy People 2020 has again included prevention and control of HTN as one of the most critical public health goals. [4][5][6] Although this initiative lacks a focus on reducing racial/ethnic differences, numerous population-based studies have identified disparities in the prevalence of HTN, with non-Hispanic Blacks having the highest prevalence of HTN (32.8%-42.1%) 1,2,7,8 , while other racial/ethnic groups have a fairly similar range of prevalence estimates: non-Hispanic Whites (21.1%-29.8%), 1,2,[7][8][9] Hispanics (24.7%-29.3%), 1,[7][8][9] and nonHispanic Asians (24.7%-25.6%). 8,10 To date, many of the populationbased studies examining racial/ethnic differences in HTN prevalence have focused on differences between broad minority groups; few have examined differences in Asian and Hispanic sub-populations.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Despite this effort, several studies have raised the concern of racial and ethnic inequalities in terms of hypertension treatment and control. [3][4][5][6] Although suboptimal insurance coverage and poor access to health care are most widely accepted determinants of health disparities, the causes of racial inequalities are complex and require systematic studies to bridge the gap in achieving universal highquality clinical outcomes. We sought to examine the racial differences in hypertension treatment and control, describe antihypertensive drug utilization patterns, and explore potential causes of racial disparities in these measures.…”
mentioning
confidence: 99%